Władza i rodowód. O wizerunku władcy w staroserbskiej literaturze - Lis-Wielgosz, Izabela (Wydawnictwo Naukowe UAM, 2013)
The article refers to a problem of relationship between authority and genealogy, and to their specific functioning in the Old Serbian literature,that is in other words, in the hagiographical, historiographical, and hymnic texts. In all those works, the combination of the both ideas undoubtedly serves the ideological creation, regarding the image of sovereign together with the exposition of his extra-ordinary lineage and destiny which are tied to his place and role in the space of history, politics, religion, and culture. In the literature, this peculiar relationship is expressed by the two characteristic constructions of dynasty and genealogy. With regard to this representation, the dynastic construction is based on the model of biblical motif concerning Jesse’s stem and functions as the saint osierof the family of Nemanjić. As for the second construction, of genealogy, it reveals itself as a component of the classical myth of historiography that determines the beginnings namely, the Serbian sovereign’s mythical genesis that also concerns all his charismatic, saint family.
Authority and Lineage. On the Image of Sovereign in the Old Serbian Literature
Keywords: authority; lineage; holiness; sovereign; Old Serbian Literature; hagiographical texts; historiographical texts; hymnic texts; state; orthodox Church; dynasty